Predictors of Suboptimal Adherence Among Children on Antiretroviral Therapy in Southern Ethiopia: A Multicenter Retrospective Follow-Up Study - Tamirat Gezahegn Guyo; Fasika Merid; Temesgen Mohammed Toma (Frontiers Media S.A., 2023)
Objectives: Despite increased access to and availability of antiretroviral therapy, the program's effectiveness is primarily affected by treatment adherence. Therefore, this study aimed to determine the magnitude and predictors of suboptimal adherence among children on ART in Southern Ethiopia.Methods: A multicenter retrospective study was conducted among human immunodeficiency virus (HIV) infected children in Gamo and South Omo zone public health facilities. To identify factors associated with suboptimal adherence, a binary logistic regression model was fitted. Variables with a p-value ≤0.25 in bivariable logistic regression analysis were included in multivariable logistic regression analysis. p-value <0.05 was used to declare statistical significance.Results: The suboptimal adherence was determined to be 30.3% (95% CI: 25.5%, 35.6%). Advanced clinical stage, hemoglobin level <10 mg/dL, unchanged initial regimen, and non-disclosure of HIV sero-status were significant predictors of suboptimal adherence.Conclusion: Suboptimal adherence is a significant public health problem in the study setting. Therefore, designing interventions towards improving adherence is needed especially for children with poor clinical characteristics.